2004
DOI: 10.1002/mrm.20026
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the renal perfusion and glomerular filtration rate from the renal impulse response obtained with MRI

Abstract: The aim of this study was to assess the importance of deconvolution for the calculation of renal perfusion and glomerular filtration rate (GFR) on the basis of concentration-time curves as measured with perfusion MRI. Six rabbits were scanned dynamically after injection of a gadolinium chelate. Concentration-time curves were generated by manually drawing regions of interest in the aorta and the renal cortex. To remove the dependency on the arterial input function, a regularized structured total least-squares d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
108
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(113 citation statements)
references
References 37 publications
4
108
1
Order By: Relevance
“…Several approaches have been proposed to analyze renography data, including the upslope method (2), deconvolution (3,4), the Rutland-Patlak method (5,6), and renal kinetic modeling (7)(8)(9)(10). The key prerequisite is the ability to segment dynamic MR images into functional regions (i.e., the cortical and medullary compartments).…”
mentioning
confidence: 99%
“…Several approaches have been proposed to analyze renography data, including the upslope method (2), deconvolution (3,4), the Rutland-Patlak method (5,6), and renal kinetic modeling (7)(8)(9)(10). The key prerequisite is the ability to segment dynamic MR images into functional regions (i.e., the cortical and medullary compartments).…”
mentioning
confidence: 99%
“…Dynamic contrast enhanced MRI is a promising noninvasive method for imaging renal perfusion and function (1)(2)(3)(4)(5), since it avoids the use of ionizing radiation and combines high temporal and spatial resolution. Moreover, Gd-DTPA is very well tolerated, not nephrotoxic, and has properties comparable to the radioisotopic 99mTc-DTPA (6,7).…”
mentioning
confidence: 99%
“…Experiments with a rabbit model (1) have shown that Gd-DTPA enhanced bolus tracking and a deconvolution analysis of ROI signals permit quantitative measures of perfusion and filtration, independent of the effect of the shape and size of the bolus. On the other hand, results obtained with an intravascular contrast agent have shown that a pixel-by-pixel approach to perfusion quantification can be a useful tool for distinguishing normality from renal artery stenosis in dogs as well as humans (2,3).…”
mentioning
confidence: 99%
“…Whole kidney GFR was estimated from the calculated tubular flow per mL and assuming a cortical volume of 70.4 cm 3 in adolescent healthy pigs (26,27).…”
Section: Postprocessingmentioning
confidence: 99%